Total Quality Management Practices in Accredited and ISO Certified Management College Libraries: A Comparative Study - David, Johnson; Adityakumari, H. (Journal of Information and Knowledge)
This paper aims to analyse and evaluate the difference in practicing of TQM application of NBA, NAAC, ISO and six sigma in Management and professional college libraries. The authors investigate through a survey based on a structured questionnaire. The study confirmed that most of the past studies have found that TQM has a deep impact on library performance. Several researchers have also looked at the concept of standardization of quality (ISO 9000 Certification and Accreditation) in relation to the implementation of TQM. This study compared TQM practices in accredited and ISO certified Management College libraries. The data were collected from 57 libraries of management colleges using a structured questionnaire. Independent samples 't' test and One way ANOVA were employed to find out difference between ISO and non-ISO certified institutions in their TQM, as well as difference between libraries accredited by different agencies. Results revealed that those management libraries with ISO certification had higher TQM practices compared to management libraries without ISO certification. Further, management libraries with EQUIS accreditation had least TQM and libraries with NBA accreditation had highest TQM practices. The authors conclude the article by providing suggestions to improve the TQM services in management libraries.